PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI MOBILE LEARNING BERSISTEM OPERASI ANDROID - Rachmat Efendi (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractLearning media are all things used in learning activities to convey information during the learning process. This study aims to describe the feasibility of an Android mobile learning application, describe student responses to the Android mobile learning application, and evaluate student learning outcomes towards a mobile learning application with an Android operating system. Research type Research & Development 4D model from Thiagarajan. The research method concerned only three stages, defining, designing, and developing. Material validity instrument was collected from content experts, the media, and the assessment of questions. The research output shows that the development of a mobile learning application with an Android operating system is considered very decent based on average expert validation. Mobile learning applications are considered “very good” at learning because the development that carried out can increase the interest of students in the learning process. According to the findings of the student response study, 97.53per cent of the interest in the product and the disparity in learning outcomes between the experimental group was 94.44 and the control group was 66.66 percent.Keywords: Mobile Learning, Learning Outcomes, Operating System, Android